Crisis de sistema(s) y transiciones del fin del siglo XX en las áreas semiperiféricas del mundo - Harsányi, Iván (Acta Hispanica, 2016)
The nature of the transitions in these regions of the world (Southern Europe, Central Eastern Europe and Latin America) reflects their historical antecedents, the particularities of the period when they occured, and the current balance of the respective international forces. The distinctive feature of the Central-Eastern European transitions is that these changes were not limited to the transformations of their respective political regimes, but affected their entire socioeconomic structure, this is why they served as origins of tensions that lasted for various decades. In each of these countries, different types of dictatorial or authoritarian regimes were established in the first half of the 20th century, and played a different role in World War II. With the exception of Yugoslavia, they all took part in the military and economic organizations of the Eastern block (the Warsaw Pact, COMECON), within the context of the bipolar system of powers. Due to their semiperipheral character, most of them had limited opportunities to catch up with the more developed countries even after the transition, and their steps taken in this direction were hesitants. The comparison between their respective transitions is further complicated by their different political-cultural traditions and by the consequences of the globalization of societies, due to the effects of the serious global economic and financial crisis that unfolded in 2008 and is still present nowadays.